PENATAAN KAMERA DALAM PEMILIHAN KOMPOSISI GAMBAR FILM DOKUMENTER TARI BARIS MEMEDI PADA PROGRAM BALI SANTHI INEWS BALI - Ni Nyoman Trisna Dewi Cahyani; Ni Kadek Dwiyani; Gede Pasek Putra Adnyana Yasa (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2023)
Television stations present various types of interesting and varied programs every day. Bali Santhi iNews Bali is a program that investigates the theme of Balinese culture. The Bali Santhi program displays the process of Balinese traditional ceremonies from the beginning to the end of the event by presenting many Balinese ceremonies that are in accordance with facts that have high attractiveness. Baris Memedi dance is one of the Balinese dance arts that is included in the group of sacred ceremonial dances that are performed at the atiwa-tiwa, or mass recitation, in Jatiluwih Penebel Traditional Village, Tabanan. The Baris Memedi documentary film was created with the intention of becoming a medium for public information about the many Balinese cultures that exist but are not widely known by the wider community, including, of course, the Balinese people. Shooting composition is an important aspect of the beauty of a film. The creation of the Tari Baris Memedi documentary film requires several stages that require a long process, starting from pre-production, production, and post-production. The results of the creation show that the arrangement of the images in the Tari Baris Memedi Documentary is divided into several parts, namely the camera angle, shot size, and also the composition, each of which has a message and meaning implied in it. This work is expected to be able to provide information to the Balinese people about Balinese culture in Bali and convey messages through the arrangement of images created by the author.